Reframing reformation: understanding religious difference in early modern Europe - Terpstra, Nicholas (Publications of the Centre for Reformation and Renaissance Studies / Essays and studies, 2020)
"What is Reformation, and where? Who does it impact, and how? This collection offers a sustained, comparative, and interdisciplinary exploration of religious transformations in the early modern world. The Reformation was once framed as a sixteenth-century European Protestant and Catholic phenomenon, but scholars now follow its impacts across different confessions, faiths, time periods, and geographical areas. The essays in this volume track global developments and compare the many ways in which Reformation movements shaped relations between Christians, Jews, Muslims, Buddhists, and aboriginal groups in the Americas. The authors highlight the various negotiations, tensions, and contacts that developed across social, gender, and religious lines in different parts of the early modern world. Working with themes of Framing, Mobilizing, and Transcending Difference, they explore how different convictions about religious reform and different approaches to it shaped both social action and cross-confessional encounters."--